A case report: corheart 6 biventricular assist device therapy for end-stage heart failure in dilated cardiomyopathy - Ding, Qiuju; Chen, Cheng; Xu, Zhenjun; Zhang, Ning; Pan, Jun; Ge, Min (Frontiers in Cardiovascular Medicine, 2025)
Approximately one-third of patients with end-stage heart failure (ESHF) experience biventricular failure. Left ventricular assist devices (LVADs) are employed as a salvage therapy for individuals with advanced heart failure. The onset of right ventricular failure complicates the postoperative management of patients receiving LVAD support. Currently, no right ventricular assist device is specifically designed for isolated right heart failure support, necessitating cardiac surgeons worldwide to adopt various improvised methods using LVADs for right ventricular assistance. This report details the first case at Nanjing Drum Tower Hospital in which a Corheart 6 magnetically levitated LVAD was successfully employed for biventricular assistance in a patient with ESHF secondary to dilated cardiomyopathy.